Stimulation of Consumer Cooperation Development in Small Forms of Fruits and Vegetables Production - Kalchenko, Serhii; Кальченко, Сергій Володимирович; Кальченко, Сергей Владимирович; Kolokolchykova, Iryna; Колокольчикова, Ірина Володимирівна; Колокольчикова, Ирина Владимировна; Legeza, Daria; Легеза, Дар'я Георгіївна; Легеза, Дарья Георгиевна; Yeremenko, Denys; Єременко, Денис Володимирович; Еременко, Денис Владимирович; et al. (My University, 2020)
The efficiency of small gardening is considered in this paper. The importance of peasant households for the Ukrainian village is justified. The necessity measures facilitating the efficiency of family agricultural production was proved. The international practices of the functioning of peasant households were analyzed. The recommendations such as the assessment of small agricultural development were proposed. The marketability level, its share in the revenue is the important criteria. The necessity of the peasant households unions on cooperatives was proved. The servicing cooperative model was proposed. Its mission is a provision of sale of production. Amendments in the efficiency of the economic activity, in budget of the farming families were determined. The recommendations proposed enables to improve the peasants' well-being level, to influence positively on the vegetables market. Transition of peasant households to the entrepreneurial basis develop of servicing cooperation in small agricultural is presented as well.
Keywords: peasant household; servicing cooperation; agricultural production